Design of IoT-Based One Axis Passive Solar Tracker - Fitriyanah, Dwi Nur; Abyrahman, Bramasta Ghozi; Abadi, Imam (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Photovoltaic (PV) is a device that has the ability to convert solar energy into electrical energy. The most popular way to improve performance in PV is to add solar tracker technology. There are 2 solar tracker methods, namely passive and active, in this study focuses on the passive method where the slope angle of the PV is calculated using astronomical calculations. The difference in previous research is that the PV tilt angle can be adjusted via cellphone, it has a function if the Tracker system is damaged it can be replaced first using this system. In this study, the INA219 sensor is used to measure the current, voltage, and power at the PV output, and the GY52MPU 6050 sensor is used to measure the PV slope. The results obtained from this study are the accuracy value of the INA219 sensor is 98.67% for power and 97.67% for current and there is an error of 1.33% for power and an error of 2.33% for current values. There is also an accuracy value of the GY52MPU6050 sensor which is 99.6% and an error of 0.4%. IoT is also carried out where if the current value is greater, the delay that occurs is also higher. There is also an increase in performance between fixed-based and tracker by 21% in sunny conditions, and 15% in cloudy conditions.